Family lore : a novel [large type] - Acevedo, Elizabeth (Thorndike Press large print top shelf., 2023)
"Sisters Matilde, Pastora, Camila, and Flor thought they knew each other well, until Flor--inspired by a documentary her daughter Ona made her watch--decides she wants a living wake, a party to bring her family and community together and celebrate the long life she's led, while she's still around to enjoy it. She's not ill, as far as anybody knows, but Flor does have a gift: she can predict, to the day, when someone will die. Has she foreseen her own death, or someone else's, or does she have other motives? She refuses to say. But Flor isn't the only person with secrets. Matilde has tried for decades to cover the extent of her husband's infidelity, but she now must confront the true state of her marriage. Pastora is typically the most reserved sister, but Flor's wake motivates this driven woman to attempt to solve her sibling's problems. And the next generation, cousins Ona and Yadi, face tumult of their own: Yadi, reuniting with her first love, who was imprisoned when they were both still kids; and Ona, married for years and attempting to conceive. Ona must decide whether it's worth it to keep trying-in having a child, and in the anthropology research that's begun to feel lackluster. Spanning the three days prior to the wake, FAMILY LORE traces the lives of each of the Marte women, weaving together past and present, the Dominican Republic and New York City. Told with Elizabeth Acevedo's inimitable voice, this is an indelible portrait of sisters and cousins, aunts and nieces--one family's journey through their history helping them better navigate all that is to come"--